AGRICULTURAL LAND AS A PUBLIC GOOD - Renata Marks-Bielska (Polityki Europejskie, Finanse i Marketing)
The aim of this article isto discuss the multifunctionality of agricultural land and its importance. Amonographic method has been employed to elaborate on the research subject. A perusal of the relevant national and foreign literature has confirmed that agricultural land is a specificgood with characteristics of both private and public goods. Agricultural land is a unique typeof public good, a finding thatsupportsthe claim that adivision of goods into strictly market and public ones is an excessive oversimplification. The so-called “mixed goods”(including substantive ones)which are shaped by the interplay of market forces,as well as the interests of groups and the stateoccupy an important position. The goods regarded to have positive externaleffects or a particular value to society are supported by the state orby economic entities (e.g.,specific instruments of the Common Agricultural Policy). The unique importance of agricultural land as an asset withboth public and market characteristicsstems notonly from its particular features, but also from the fact that it pro-vides space for the achievement of public interest.Agricultural land plays many important rolesthat areessential not only to food producers,for whom it isthe baseof agricultural production, but also tothe entire society.